Laser Scanning based methodology for on-line detection of inclusion in prepreg based composite aircraft manufacturing. (2020) - Nayak, Divyashree; Ramesh, Vandana; Augustin, M.J.; Gupta, Nitesh; Ramesh Kumar, M.; Patil, Chandrasekhar M.
Abstract: Among different manufacturing process of composite aircraft structures, pre-preg based manual layup is commonly used method. One of the major concerns during layup process is the accidental occurrence of inclusions like release film, pre-preg backup film etc., Presently, inclusions are detected through visual inspection by clean room inspector. As these inclusions are very thin, they may go unnoticed by the inspector. These inclusions can cause delamination or disbonds during the service life of an aircraft leading to the rejection of component resulting in loss of time and money. This raises requirement for a semi-automated/automated system to detect inclusion in a faster, efficient and reliable manner during layup process. This paper presents 3D laser scanner based methodology for detecting inclusions based on curvature analysis of point cloud data as thickness variation.